THE SECOND-PERSON PERSPECTIVE IN VIDEO GAMES - Liz Gutiérrez, Manuel (Analysis. Journal of Philosophical Research, 2024)
We examine the notion of personal perspectives—first-person, second-person, and third-person—and apply this analysis to the personal perspectives found in certain phenomena of popular culture, particularly within the field of video games. A distinction is drawn between the surface structure and the deep structure of personal perspectives, as well as another distinction according to their differing performative force, in a very generic sense but sufficient for our purposes. Second-person perspectives will have significant relevance. Even immersed in the virtual reality of a certain kind of universal video game, the genuine adoption of second-person perspectives guarantees the existence of an external world with at least some personal entities possessing conscious minds. This insight refines certain ideas recently advanced by David Chalmers. Indeed, we can assume his thesis that virtual reality is genuine reality. However, the capacity to adopt second-person perspectives is incompatible with both the idea that everything could be a simulation and the idea that we cannot know that it is not.